2021
DOI: 10.3390/cancers13122985
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Cells Shuttle Extracellular Vesicles Containing Oncogenic Mutant p53 Proteins to the Tumor Microenvironment

Abstract: Extracellular vesicles (EVs) shed by cancer cells play a major role in mediating the transfer of molecular information by reprogramming the tumor microenvironment (TME). TP53 (encoding the p53 protein) is the most mutated gene across many cancer types. Mutations in TP53 not only result in the loss of its tumor-suppressive properties but also results in the acquisition of novel gain-of-functions (GOF) that promote the growth of cancer cells. Here, we demonstrate that GOF mutant p53 proteins can be transferred v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…For instance, p53 (WT or mutant) regulates exosomal secretion by participating in exosome biogenesis, promoting exosome secretion, and altering exosome content to modify cell secretome and remodel TME [ 38 41 ]. Moreover, mutant p53 is secreted into the TME by several tumor cells, including cancer-associated fibroblasts [ 42 , 43 ]. A previous study demonstrated the biological role of EV-mediated p53 WT secretion [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, p53 (WT or mutant) regulates exosomal secretion by participating in exosome biogenesis, promoting exosome secretion, and altering exosome content to modify cell secretome and remodel TME [ 38 41 ]. Moreover, mutant p53 is secreted into the TME by several tumor cells, including cancer-associated fibroblasts [ 42 , 43 ]. A previous study demonstrated the biological role of EV-mediated p53 WT secretion [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study revealed that mutant p53 can be transported between cells through EVs to alter the tumor microenvironment, which could trigger immunosuppression ( 71 ). A previous study has shown that mutant p53 proteins are expressed in pancreatic, lung, and colon cancer cell lines; these proteins can be selectively packaged into EVs and then affect the reprogramming of the tumor microenvironment ( 72 ). It has been shown that exosomal miR-1246 can transfer the mutant p53 protein product from cancer cells to neighboring cancer cells and macrophages, leading to alterations in the tumor microenvironment ( 73 ).…”
Section: Mutant P53 Gof Activities and Mechanisms In Hnsccmentioning
confidence: 99%
“…To investigate the radio-sensitivity of cancer cells based on their p53 status, we used two separate cellular models: PANC-1 cells (pancreatic ductal adenocarcinoma, PDAC) as well as HCT116 cells (colorectal cancer, CRC). For the PANC-1, harboring the gain-of-function p53 mutant in the 273 position (arginine to histidine, R273H), we used negative control cells where the mutant p53 was knocked out (KO) using crisper as described in (43). For the HCT116, harboring the gain-of-function p53 mutant in the 248 position (arginine to tryptophan, R248W), we used the isogenic set of WT (p53 +/+) to compare with the mutant cells as described in (44).…”
Section: Mutant P53 Cancer Cells Confer Radio-sensitivity When Expose...mentioning
confidence: 99%